Metabolic heterogeneity of brain tumor cells of proneural and mesenchymal origin - Seliger, Corinna; Meyer, Anne-Louise; Leidgens, Verena; Rauer, Lisa; Möckel, Sylvia; Jachnik, Birgit; Proske, Judith; Dettmer-Wilde, Katja; Rothhammer-Hampl, Tanja; Kaulen, Leon D.; Riemenschneider, Markus J.; Oefner, Peter J.; et al. (International journal of molecular sciences, 2022)
Brain-tumor-initiating cells (BTICs) of proneural and mesenchymal origin contribute to the highly malignant phenotype of glioblastoma (GB) and resistance to current therapies. BTICs of different subtypes were challenged with oxidative phosphorylation (OXPHOS) inhibition with metformin to assess the differential effects of metabolic intervention on key resistance features. Whereas mesenchymal BTICs varied according to their invasiveness, they were in general more glycolytic and less responsive to metformin. Proneural BTICs were less invasive, catabolized glucose more via the pentose phosphate pathway, and responded better to metformin. Targeting glycolysis may be a promising approach to inhibit tumor cells of mesenchymal origin, whereas proneural cells are more responsive to OXPHOS inhibition. Future clinical trials exploring metabolic interventions should account for metabolic heterogeneity of brain tumors.